Rationale and design of the Anal HPV, HIV and Aging (AHHA) study: Protocol for a prospective study of anal HPV infection and HSIL among men who have sex (MSM) or trans women living with and without HIV, ages 50 and older - Hernandez, Alexandra L.; Weatherly, Christopher Scott; Gonzalez, Ryan; Farhat, Sepideh; Da Costa, Maria; Calderon, Joanne; Kauffman, Jason; Akha, Arezou Sadighi; Hilton, Joan F.; Palefsky, Joel M. (Frontiers in Epidemiology, 2022)
Introduction: More than half of people living with HIV in the US are 50+ years old. Despite the benefits of antiretroviral therapy, older individuals with HIV are at higher risk for illnesses than their HIV-negative counterparts. Anal cancer, anal high-grade squamous intraepithelial lesions (HSIL), and anal HPV-16 infection occur most frequently among men who have sex with men living with HIV (MSMLWH). Men aged 60+ are 3-fold more likely to be diagnosed with anal cancer compared with men of all ages. Despite the increasing risk of anal cancer with age and HIV, little is known about the relationships among aging, HPV infection, HSIL and HIV. Methods and Analysis: The Anal HPV, HIV, and Aging (AHHA) Study is a two-phase project to evaluate the relationships among anal HPV infection, HSIL, HIV infection, and biomarkers of biological aging in MSM over the age of 50 years. Phase 1 will estimate the cross-sectional prevalence of both anal HPV infection and HSIL, based on outcomes of anal HPV DNA testing, and high-resolution anoscopy with biopsy. We will also study associations with study outcomes and serological biomarkers of inflammation (interleukin-6, C-reactive protein, D-dimer) and with the Veterans Aging Cohort Study Index and the Fried Frailty Phenotype using multivariable models. MSMLWH (n=150) and HIV-negative MSM (n=150) will be enrolled. The 3-year Phase 2 longitudinal sample restricted to HSIL-negative and anal HPV-16 DNA-negative participants will estimate the 3-year incidence of both anal HSIL and anal HPV, stratified by HIV status through Cox proportional hazards regression. The effect of biomarkers of inflammation and markers of aging on study outcomes will be evaluated through multivariable repeated measures models stratified by HIV status. Ethics and Dissemination: This protocol was approved by the University of California, San Francisco Institutional Review Board (IRB:16-18966). Results will be disseminated through presentations at national/international scientific conferences and publication in peer-reviewed journals.